The Cambridge companion to Mario Vargas Llosa - Kristal, Efraín; King, John (Cambridge companions to literature., 2012)
"One of the major novelists in world literature over the last five decades, Mario Vargas Llosa (b. 1936) is also one of Latin America's most engaging public intellectuals, a critic of art and culture, and a playwright of distinction. This Companion's chapters chart the development of Vargas Llosa's writings from his rise to prominence in the early sixties to the award of the Nobel Prize for Literature in 2010. The volume traces the development of his literary trajectory, and the ways in which he has reinvented himself as a writer. His vast output of narrative fiction is the main focus, but the connections between his concerns as a creative writer and his rich career as a cultural and political figure are also teased out in this engaging, informative book"--Provided by publisher.